Another perspective on the forecasting of economic processes - Mičeková, Mária (Communications - Scientific letters of the University of Zilina, 1999)
This article describes methods used from dynamic systems theory in solving the tasks of forecasting economic processes. The possibility of using theoretical methods in forecasting is demonstrated with the example of the prediction regarding the development of the rate of exchange between the USD and the SK.